2019
DOI: 10.5114/ceji.2019.87498
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the level of selected parameters of inflammation, circulating immune complexes, and related indicators (neutrophil/lymphocyte, platelet/lymphocyte, CRP/CIC) in patients with obstructive diseases

Abstract: IntroductionChronic obstructive pulmonary disease (COPD) is an inflammatory disorder of the airways. An important element of COPD assessment is the evaluation of immune mechanisms involved in non-specific and specific response to ongoing inflammation.Aim of the studyTo evaluate the level of selected inflammatory and immunological parameters in patients with COPD, including C-reactive protein (CRP) and circulating immune complexes (CIC), as well as CRP/CIC index.Material and methodsThe study group consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
3
19
0
1
Order By: Relevance
“…In previous studies, the possible causes of platelet changes in COVID-19 patients were analyzed and it was shown that the lung may be one of the organs in which mature megakaryocytes release platelets and that thrombocytopenia in patients with SARS-CoV infection may be associated with lung damage [24]. Injury of lung tissue and pulmonary endothelial cells can lead to activation, aggregation, and retention of platelets in the lung, and the formation of thrombus at the injured site, which may lead to the depletion of platelets and megakaryocytes, resulting in decreased platelet production and increased consumption [25].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the possible causes of platelet changes in COVID-19 patients were analyzed and it was shown that the lung may be one of the organs in which mature megakaryocytes release platelets and that thrombocytopenia in patients with SARS-CoV infection may be associated with lung damage [24]. Injury of lung tissue and pulmonary endothelial cells can lead to activation, aggregation, and retention of platelets in the lung, and the formation of thrombus at the injured site, which may lead to the depletion of platelets and megakaryocytes, resulting in decreased platelet production and increased consumption [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several causes can induce platelet deficiency, such as the direct SARS-CoV2 infection of haematopoietic cells or bone marrow stromal cells, leading to haematopoietic inhibition [30]. The lung injury could also contribute to the platelet depletion due to the activation, aggregation, and retention of platelets in the lung, and the formation of thrombus at the injured site, leading to decreased platelet production and increased consumption [31,32].…”
Section: Haematological Alterationsmentioning
confidence: 99%
“…(b) Previous studies have shown that the lung may be one of the organs in which mature megakaryocytes release platelets and that thrombocytopenia in patients with SARS-CoV infection may be associated with lung damage 19,20. Extensive alveolar damage both occurred in patients with COVID-19 and SARS, and lung tissue damage was induced by a viral infection and high flow of oxygen.…”
mentioning
confidence: 99%
“…Extensive alveolar damage both occurred in patients with COVID-19 and SARS, and lung tissue damage was induced by a viral infection and high flow of oxygen. Injury of lung tissue and pulmonary endothelial cells can lead to activation, aggregation, and retention of platelets in the lung, and the formation of thrombus at the injured site, which may lead to the depletion of platelets and megakaryocytes, resulting in decreased platelet production and increased consumption 20. 21 (c) Huang et al 22 believed that patients with COVID-19 had a large amount of IL-1, F I G U R E 4 Pneumonitis worsens with platelet-to-lymphocyte ratio difference (ΔPLR) elevation in some patients.…”
mentioning
confidence: 99%